(untitled) - Sugar, Bert (Hoboken, N.J., 2003)
Bert Sugar wears his hat and waves his cigar and looks like some old-time fight manager. But this is far from being true. Bert Sugar is a brilliant man. And pride would not allow him to do a book that doesn’t reflect this much work and care for English: ‘Robinson Crusoe without a boat.’ The reader gets a big break with this one
Keywords: Horse racing,Đua ngựa; United States,Hoa Kỳ